A high-quality assembled genome and its comparative analysis decode the adaptive molecular mechanism of the number one Chinese cotton variety CRI-12. (1st April 2022) - Lu, Xuke; Chen, Xiugui; Wang, Delong; Yin, Zujun; Wang, Junjuan; Fu, Xiaoqiong; Wang, Shuai; Guo, Lixue; Zhao, Lanjie; Cui, Ruifeng; Dai, Maohua; Rui, Cun; et al.
Abstract: Background: Gossypium hirsutum L. is the most widely cultivated cotton species, and a high-quality reference genome would be a huge boost for researching the molecular mechanism of agronomic traits in cotton. Findings: Here, Pacific Biosciences and Hi-C sequencing technologies were used to assemble a new upland cotton genome of the No. 1 Chinese cotton variety CRI-12. We generated a high-quality assembled CRI-12 genome of 2.31 Gb with a contig N50 of 19.65 Mb, which was superior to previously reported genomes. Comparisons between CRI-12 and other reported genomes revealed 7, 966 structural variations and 7, 378 presence/absence variations. The distribution of the haplotypes among A-genome ( Gossypium arboreum ), D-genome ( Gossypium raimondii ), and AD-genome ( G. hirsutum and Gossypium barbadense ) suggested that many haplotypes were lost and recombined in the process of polyploidization. More than half of the haplotypes that correlated with different tolerances were located on chromosome D13, suggesting that this chromosome may be important for wide adaptation. Finally, it was demonstrated that DNA methylation may provide advantages in environmental adaptation through whole-genome bisulfite sequencing analysis. Conclusions: This research provides a new reference genome for molecular biology research on Gossypium hirsutum L. and helps decode the broad environmental adaptation mechanisms in the No. 1 Chinese cotton variety CRI-12.